Producción musical del tema Remember Me de Germán Arias - Arias Mantilla, Germán Andrés (2018)
In the following project of titulation has managed to document in detail, the whole process of production of the theme “Remember me”, which will try to explain in the best way each stage of the process so that, once concluded the study of this work, the reader has the ability, applying what has been learned, to develop an electronic music project of the same quality. It began by explaining the origin of House music, its history and evolution to what is now known as electronic music, currently being one of the most consumed genres worldwide. The main characteristics of the genre were investigated, analyzed and tried to be recreated within the Remember me production, however, non-common elements of the style were added. In this production it was intended to leave a bit of the traditional aesthetics of House music, with the aim of giving a more characteristic sound to the artist, then recorded real instruments, which were included as a percussive, harmonic and melodic part of the song, achieving with this an unusual proposal, but ensuring that the convergence of real and digital instruments is to the liking of the public. It took into account parameters of commercial music such as duration, BPM, structure, among others, when composing the song, so that the theme meets these characteristics to be transmitted by radio.